2020
DOI: 10.21203/rs.3.rs-58076/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Observations on echocardiographic findings in patients with COVID-19

Abstract: Background The novel coronavirus (SARS-CoV-2) has created global havoc by causing Coronavirus Disease 2019 (COVID-19). Cardiovascular involvement in COVID-19 varies from troponin rise or arrhythmia/myocarditis to fulminant cardiogenic shock. There is limited data on echocardiographic findings in such patients. We aimed to assess abnormal echocardiographic findings and contributory factors in patients with COVID-19.Methods We performed retrospective analysis of COVID-19 positive patients who underwent a transth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Tricuspid regurgitation was the most common finding followed by mitral and aortic regurgitation. These findings came in agreement with Khan et al (21) who showed that the most common abnormality was valve regurgitation, tricuspid regurgitation was the most common observed (56.5%), followed by aortic regurgitation (28.3%) and mitral regurgitation (26.1%). This could be due to direct injury to myocyte, fulminant myocarditis or myocardial infarction resulting in chordae rupture as reported by Khanduri et al (22) .…”
Section: Discussionsupporting
confidence: 92%
“…Tricuspid regurgitation was the most common finding followed by mitral and aortic regurgitation. These findings came in agreement with Khan et al (21) who showed that the most common abnormality was valve regurgitation, tricuspid regurgitation was the most common observed (56.5%), followed by aortic regurgitation (28.3%) and mitral regurgitation (26.1%). This could be due to direct injury to myocyte, fulminant myocarditis or myocardial infarction resulting in chordae rupture as reported by Khanduri et al (22) .…”
Section: Discussionsupporting
confidence: 92%
“…Significant valvular heart disease was associated with elevated sPAP concentrations (moderate or greater severity). According to the findings by Khan et al (15) the majority of patients with abnormal transthoracic echocardiography (TTE) had valvular heart disease but no further pathology.…”
Section: Echocardiographic Manifestations In Covid-19mentioning
confidence: 99%
“…Numerous studies have used troponin levels, ECG abnormalities, and echocardiography features to explain the COVID-19-related cardiac injury in detail (13)(14)(15) . There is no link between troponin and abnormal TTE, and the underlying causes of cardiac dysfunction as they relate to abnormal TTE are probably complicated.…”
Section: Echocardiographic Manifestations In Covid-19mentioning
confidence: 99%
“…These valvular diseases more likely were present before the onset of SARS-CoV2 infection. A recent study regarding echocardiographic findings among COVID patients reported that half of them presented a significant tricuspid regurgitation followed by aortic regurgitation and mitral regurgitation 47 . Tricuspid regurgitation is the most common VHD reported in COVID-19 patients and its severity could directly reflect the impairment of the pulmonary circulation during the infection resulting in pulmonary hypertension, especially in patients with severe pneumonia and respiratory insufficiency 48 .…”
Section: Cardiac Valves and Pericardiummentioning
confidence: 99%